2023
DOI: 10.1093/hr/uhad118
|View full text |Cite
|
Sign up to set email alerts
|

UV-B promotes flavonoid biosynthesis in Ginkgo biloba by inducing the GbHY5-GbMYB1-GbFLS module

Abstract: Ginkgo biloba (ginkgo) leaves have medicinal value due to their high levels of secondary metabolites, such as flavonoids. We found that the flavonoid content in ginkgo leaves increases significantly at high altitudes (Qinghai-Tibet Plateau). Considering that high UV-B radiation is among the key environmental characteristics of the Qinghai-Tibet Plateau, we carried out simulated UV-B treatments on ginkgo seedlings and found that the flavonoid content of the leaves increased significantly following the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Consequently, species inhabiting high altitudes necessitate the adoption of multiple strategies to effectively acclimate to harsh environmental conditions. Numerous previous studies suggested that environmental factors have a significant effect on the growth and development of organisms, especially on the accumulation of their flavonoid metabolites [39][40][41]. Environmental factors contribute to the flavonoid biosynthesis of many organisms and generate economic value.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, species inhabiting high altitudes necessitate the adoption of multiple strategies to effectively acclimate to harsh environmental conditions. Numerous previous studies suggested that environmental factors have a significant effect on the growth and development of organisms, especially on the accumulation of their flavonoid metabolites [39][40][41]. Environmental factors contribute to the flavonoid biosynthesis of many organisms and generate economic value.…”
Section: Discussionmentioning
confidence: 99%
“…When plants receive high doses of UV-B radiation, the plant leaves show severe wilting and curling. In addition, certain doses of UV-B radiation cause dwarfism in plants [26,27]. The damage caused by UV-B radiation to plants is mainly caused by the accumulation of reactive oxygen species (ROS), which harm cells by damaging proteins and DNA [28,29].…”
Section: In Vitro Characterization Of Recombinant Elomt1mentioning
confidence: 99%
“…In this present study, LcFLS and UGTs were significantly upregulated in the flower buds of EEM cultivars compared to MLM cultivars. FLS is an important enzyme responsible for the production of flavonols and has been proven to play vital roles in flower coloration [55,56] and response to UV-B radiation [17,57]. FLS competes with DFR for the common substrate dihydroflavonols, leading to the production of flavonols and anthocyanins, respectively [58].…”
Section: Key Structural Genes Responsible For Differential Flavonol G...mentioning
confidence: 99%
“…Flavonoids have been demonstrated as the major UV-absorbing compound that protects plants from the detrimental effects of UV-B radiation [15][16][17]. A previous study revealed that the concentration of flavone aglycones was elevated because of increasing UV-B radiation in an Antarctic moss, Bryum argenteum [18].…”
Section: Introductionmentioning
confidence: 99%